TAKAI DAN TINGGI SEBAGAI POLISEMI : KAJIAN LINGUISTIK KOGNITIF - Wira Wahyuni, - (2021)
Abstract The study examines adjective words takai in Japanese language and tinggi in Indonesian language as polysemy. The discussion of this study includes semantic studies from the perspective of cognitive linguistics. The study aims to describe the basic meanings and extended meanings of takai and tinggi. It also describes the relationship between its basic and extended meanings of these words. The study is qualitative research with a descriptive method. Based on the results of data analysis, takai basically means high up (far up). Meanwhile, the extended meanings are high (status), high (sound), high (big), sophisticated, expensive, sharp, and very. Of the 7 meanings, high (status), high (sound)), and sharp are extended metaphorically,while high (big), expensive, sophisticated and "very" are extended metonymy. Then, the result of data analysis for the word tinggi in Indonesian language basically means high (far up). While the extended meanings are high (status), high (many), high (big), noble, expensive, increase, and arrogant. Of the 7 meanings, high (status) and arrogant are extended metaphorically, while high (many), high (big), noble, expensive, and increase are extended metonymically. Keywords : Polysemy, semantics, cognitive, linguistics